Down-regulation of immuno-linked genes in acutely dimethoate exposed Kamrupa chicken - KAFLE, ARJUN; ROY, DULAL; DEKA, DILIP; SARMA, JADAV; NATH, RITA; DUTTA, BISWAJIT; SAIKIA, REEMA; BORAH, BISWAJIT; DEBBARMA, KHUMTYA; MOHAPATRA, SANGEETA; CHAPAGAIN, MANJU (The Indian Journal of Animal Sciences, 2024)
The present study evaluated the acute toxic effects of dimethoate and its modulation on genetic expression on the immune status in Kamrupa chickens. A total of 20 Kamrupa chickens were divided into two groups, each consisting ten birds: group 1 served as control while group 2 as treatment and received a single LD50 dose (48 mg/kg body weight) of dimethoate per os. The birds were subjected to examination of haemato-biochemical and histopathological changes as well as status of genetic expression pertaining to immunity. Birds exposed to dimethoate exhibited rapid onset of depression, anorexia, diarrhea, excessive salivation, and incoordination, ultimately leading to death. Haematological analysis showed elevated haemoglobin, total erythrocytic count, total leucocytic count, and heterophil levels, with decreased lymphocyte levels. Serum enzyme analysis indicated elevated Alanine amino transferase, Aspartate amino transferase, Alkaline phosphatase, Total cholesterol, and Uric acid levels, while Serum cholinesterase levels were decreased. Postmortem examination revealed liver, kidney, and brain congestion, haemorrhage, and hypertrophy, with liver and kidney showing degenerative changes and the brain exhibiting inflammatory lesions. Gene expression studies indicated downregulation of immune-linked Avian Beta Defensin 1, Avian Beta Defensin 6, and Avian Beta Defensin 7 genes. The results of the present study suggest that acutely dimethoate exposed Kamrupa chicken had profound harmful effects with down regulation of immune-linked genes.